Corrective oral feedback on students’ errors in speaking courses - Anis Firdatul Rochma (Journal of English Language Teaching and Learning (JETLE), 2023)
It is considered essential to improve students' speaking abilities in order to communicate in English. Unfortunately, students face a variety of difficulties in acquiring their speaking skills. Despite the fact that corrective feedback is claimed to have an influence on students' performance, particularly in speaking courses, research focused explicitly on the perceptions of students and lecturers on corrective feedback in speaking courses is still rare. Employing descriptive study including observation and survey methods, the findings revealed three results: the length of oral corrective feedback given by the lecturer, the forms of oral corrective feedback offered by lecturer in speaking courses, and the types of oral corrective feedback most desired by students during speaking courses particularly students taking courses of Speaking for Social Intercultural Communication and Speaking for Academic Purposes. The present study indicates that the teachers should be able to recognize which errors to correct and which sorts of corrective feedback to employ in their speaking classes.